2002
DOI: 10.1002/pip.423
|View full text |Cite
|
Sign up to set email alerts
|

Front and rear silicon‐nitride‐passivated multicrystalline silicon solar cells with an efficiency of 18.1%

Abstract: A solar cell process designed to utilise low‐temperature plasma‐enhanced chemical vapour deposited (PECVD) silicon nitride (SiNx) films as front and rear surface passivation was applied to fabricate multicrystalline silicon (mc‐Si) solar cells. Despite the simple photolithography‐free processing sequence, an independently confirmed efficiency of 18.1% (cell area 2 × 2 cm2) was achieved. This excellent efficiency can be predominantly attributed to the superior quality of the rear surface passivation scheme cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] Now that surface passivation using silicon nitride can be made as good as that using a thermal oxide, the material is increasingly used for the fabrication of high-efficiency silicon solar cells. [17][18][19] Big advantages of silicon nitride grown by PECVD with respect to thermal oxide are the low process temperature (typically in the range 300-400 C) and the short process time (typically a few minutes). The low process temperature is particularly important in the case of mc-Si wafers, where high-temperature processing, like thermal oxidation, may cause severe degradation of the bulk lifetime of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Now that surface passivation using silicon nitride can be made as good as that using a thermal oxide, the material is increasingly used for the fabrication of high-efficiency silicon solar cells. [17][18][19] Big advantages of silicon nitride grown by PECVD with respect to thermal oxide are the low process temperature (typically in the range 300-400 C) and the short process time (typically a few minutes). The low process temperature is particularly important in the case of mc-Si wafers, where high-temperature processing, like thermal oxidation, may cause severe degradation of the bulk lifetime of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the FF improvement is still under investigation, however a possible explanation to this increase is the impact of the injection dependence of ideality factor in the voltage range between MPP and opencircuit conditions. It was suggested in 2-D simulations [6] that a higher positive insulator charge density (for example, using our 200°C deposited SiO x film) in combination with an LBSF (instead of a standard ohmic contact) can improve the cell J sc by ∼1.7 mA/cm 2 . However, this was not observed in this study, as no change in J sc was observed.…”
Section: B Aluminum Local Back Surface Field Solar Cell Resultsmentioning
confidence: 97%
“…Hence, it was demonstrated back then that the positive charge in the rear dielectric film does not detrimentally affect the Al-LBSF solar cell efficiency when a local BSF exists underneath the metal contacts. In fact, from 2-D simulation and experiments it seems that a higher positive insulator charge density can even improve the efficiency of Al-LBSF cells, by improving the short-circuit current density J sc [6], [7]. In contrast, it is often mentioned that SiN x can lead to compromised solar cell efficiency when applied on the rear of p-type Si solar cells with local rear contacts; see, e.g., [8].…”
Section: Introductionmentioning
confidence: 99%
“…A thin layer of aluminum was deposited at the front surface; the thickness was measured by thickness monitor Edward's FTM5, followed by evaporation of thick layers of aluminum and silver through a mechanical mask to form the front contact grid [12][13][14][15][16]. In the present work we used an optimized MIS mc-Si film which reduces parasitic shunting, thus the formation of the local Al-BSF could be omitted.…”
Section: Experimental Workmentioning
confidence: 99%
“…As E p increases above E g , more and more electrons from the valence band can possibly make the transition, so the overall probability of a photon being absorbed increases. Thus, the number of photons absorbed increases [12,13].…”
Section: Fig 1 Large-grains Mc-si Thin Filmmentioning
confidence: 99%